2020
DOI: 10.1016/s0140-6736(20)31144-2
|View full text |Cite
|
Sign up to set email alerts
|

Steam inhalation and paediatric burns during the COVID-19 pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…Out of all of them, 4 recovered the baseline situation before day 7, although 2 subsequently developed a late AKI. Of the other 8 patients: 3 continued in AKIN stage I at 7 th day, 1 increase to AKIN II and 4 to AKIN III [3]. Like in the study by Chen et al, we found that Early AKI patients had more TBSA% and worse severity burn scores.…”
Section: Early Acute Kidney Injury In Severe Burnssupporting
confidence: 81%
See 1 more Smart Citation
“…Out of all of them, 4 recovered the baseline situation before day 7, although 2 subsequently developed a late AKI. Of the other 8 patients: 3 continued in AKIN stage I at 7 th day, 1 increase to AKIN II and 4 to AKIN III [3]. Like in the study by Chen et al, we found that Early AKI patients had more TBSA% and worse severity burn scores.…”
Section: Early Acute Kidney Injury In Severe Burnssupporting
confidence: 81%
“…Scald injuries remain the commonest cause of paediatric burn injuries (85% in the lockdown period, 68% in the control period). Recently, our centre observed a surge in scalds directly resulting from the practice of steam inhalation during the COVID-19 pandemic, as an unprescribed method to prevent and treat infection [3].…”
mentioning
confidence: 99%
“…Also, complete or partial lockdowns in several African countries will hinder children's access to clinics and community-based immunization services (45)(46), and caregivers may avoid facility immunization visits due to fear of COVID-19 exposure. Abbas et al's benefit-risk analysis study reported that for every one excess death attributable to SARS-CoV-2 infection from exposure, 85,000 deaths could be averted among CU5 in SSA who successfully receive routine vaccinations (41).…”
Section: Vaccine-preventable Diseases (Including Diarrhea and Pneumonia)mentioning
confidence: 99%
“…In the US and in European countries, COVID-19-related movement restrictions including school closures have significantly reduced the incidence of road traffic accidents (81-82) and volume of pediatric emergency room visits (83-84). However, reports from these settings also indicate that domestic injuries (burns, accidental ingestion) have significantly increased in the same period (79,(84)(85). So far, there is little reported data on the indirect impact of COVID-19 on unintentional child injuries in SSA.…”
Section: Unintentional Injuriesmentioning
confidence: 99%
“…Worryingly, the warnings do not seem to be having the desired effect. A recent letter published in The Lancet [21] expressed concern over the increased use of steam inhalation for symptomatic treatment during the COVID-19 pandemic, with a subsequent increase in paediatric scald injuries. The authors reported 30-fold increase at their centre in the number of paediatric scalds directly resulting from steam inhalation since the start of UK lockdown.…”
Section: Discussionmentioning
confidence: 99%